2021
DOI: 10.1007/s11739-021-02840-7
|View full text |Cite
|
Sign up to set email alerts
|

PaO2/FiO2 ratio forecasts COVID-19 patients’ outcome regardless of age: a cross-sectional, monocentric study

Abstract: We studied the predictive value of the PaO2/FiO2 ratio for classifying COVID-19-positive patients who will develop severe clinical outcomes. One hundred fifty patients were recruited and categorized into two distinct populations (“A” and “B”), according to the indications given by the World Health Organization. Patients belonging the population “A” presented with mild disease not requiring oxygen support, whereas population “B” presented with a severe disease needing oxygen support. The AUC curve of PaO2/FiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…We attribute this result to our early application of HFNO or CPAP. In two recent cohort studies, they were able to determine the cut-off value of the PaO 2 /FiO 2 ratio as 274 mmHg in patients who developed ARF due to COVID-19 pneumonia (27,28). We also obtained similar findings in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We attribute this result to our early application of HFNO or CPAP. In two recent cohort studies, they were able to determine the cut-off value of the PaO 2 /FiO 2 ratio as 274 mmHg in patients who developed ARF due to COVID-19 pneumonia (27,28). We also obtained similar findings in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Some depend on advances in research and consensus or in political decision making. For instance, a worldwide initiative to agree on a global definition of sarcopenia is ongoing (28) and updated clinical guidelines are needed. Also, sarcopenia needs to be included in the WHO International Classification of Diseasesat present it is only listed in the version named Clinical Modification and the latest version ICD-11 does not properly include sarcopenia.…”
mentioning
confidence: 99%
“…All patients in the experimental group exhibited rapid respiratory decompensation at the time of treatment initiation (mean PaO 2 /FiO 2 < 150). Typically, these patients with COVID-19 are characterized by a severe disease course, lengthy hospitalization, and high mortality rate (26)(27)(28). In this "difficult-to-treat" group of patients with COVID-19, we observed a beneficial trend for AMY-101 therapy added to standard dexamethasone and low-molecular weight heparin (LMWH) treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Airway microbiota were altered in patients with burns and inhalation injury, and the abundance of Streptococcaceae and Enterobacteriaceae increased by 30% in hypoxemia patients compared to patients with the partial pressure of arterial oxygen/fraction of inspired oxygen (PaO 2 /FiO 2 ) ratio of more than 300; among the patients with PaO 2 /FiO 2 ratio ≤300, Prevotella melaninogenica and Corynebacterium genus-level were significantly enriched ( Walsh et al, 2017 ; Walton et al, 2021 ). Furthermore, PaO 2 /FiO 2 < 274 mmHg is considered to be a reliable prognostic biomarker for COVID-19 patients ( Sinatti et al, 2021 ). In a recent study in mice, it was found that after a respiratory infection, the relative abundance of Bacteroides increased and Firmicutes decreased ( Groves et al, 2018 ).…”
Section: Mechanism Of Interaction Of Gut-lung Axismentioning
confidence: 99%